Winter and spring controls on the summer food web of the coastal West Antarctic Peninsula - Saba, Grace K.; Fraser, William R.; Saba, Vincent S.; Iannuzzi, Richard A.; Coleman, Kaycee E.; Doney, Scott C.; Ducklow, Hugh W.; Martinson, Douglas G.; Miles, Travis N.; Patterson-Fraser, Donna L.; Stammerjohn, Sharon E.; Steinberg, Deborah K.; et al. (Nature communications, 2014)
Understanding the mechanisms by which climate variability affects multiple trophic levels in food webs is essential for determining ecosystem responses to climate change. Here we use over two decades of data collected by the Palmer Long Term Ecological Research program (PAL-LTER) to determine how large-scale climate and local physical forcing affect phytoplankton, zooplankton and an apex predator along the West Antarctic Peninsula (WAP). We show that positive anomalies in chlorophyll- a (chl- a ) at Palmer Station, occurring every 4–6 years, are constrained by physical processes in the preceding winter/spring and a negative phase of the Southern Annular Mode (SAM). Favorable conditions for phytoplankton included increased winter ice extent and duration, reduced spring/summer winds, and increased water column stability via enhanced salinity-driven density gradients. Years of positive chl- a anomalies are associated with the initiation of a robust krill cohort the following summer, which is evident in Adélie penguin diets, thus demonstrating tight trophic coupling. Projected climate change in this region may have a significant, negative impact on phytoplankton biomass, krill recruitment and upper trophic level predators in this coastal Antarctic ecosystem. The Western Antarctic Peninsular is subject to climate change, including increased winter temperatures and melting sea ice. In this study, the authors demonstrate that climate change in this area effects bacteria and phytoplankton levels, which culminates in an altered diet for the apex predator, the Adélie penguin.